Perbandingan Kemudahan Pemasangan Laryngeal Mask Airway antara Teknik Baku disertai Penekanan Lidah dengan Teknik Baku - Marsaban, Arif HM; Martaria, Nency; Firdaus, Riyadh; Cahyadi, Arief (Majalah Anestesia dan Critical Care, 2014)
Laryngeal mask airway (LMA) merupakan suatu alat bantu jalan napas. Teknik baku pemasangan LMA disertai penekanan lidah memberikan angka keberhasilan pemasangan 100%. Penelitian ini bertujuan membandingan kemudahan dan komplikasi pemasangan LMA menggunakan teknik baku dengan penekanan lidah dibandingkan dengan teknik baku. Penelitian ini merupakan studi uji klinis acak tersamar tunggal yang dilakukan antara Mei – Juni 2013 di RSCM, pada 80 pasien dewasa yang menjalani operasi elektif dengan anestesia umum menggunakan LMA. Pada 40 pasien mengalami pemasangan LMA dengan teknik baku disertai penekanan lidah dan 40 pasien dengan teknik baku. Upaya pemasangan dan kemudahan dicatat dan dinilai. Pemasangan mudah bila ≤2 kali. Komplikasi pemasangan berupa noda darah, nyeri menelan dan nyeri tenggorokan dicatat dan dinilai. Analisis statistik dilakukan dengan uji chi-kuadrat dan eksak fisher. Batas kemaknaan untuk semua uji adalah p <0,05. Perbandingan proporsi keberhasilan upaya pemasangan pertama dan kedua antara kelompok teknik baku disertai penekanan lidah dan teknik baku adalah 87,5% banding 65% dan 100% banding 97,5%, secara berurutan. Pemasangan LMA dengan teknik baku disertai penekanan lidah tidak lebih mudah dibanding dengan teknik baku. Kekerapan komplikasi yang berbeda bermakna berupa noda darah 0% pada teknik baku disertai penekanan lidah dan 6,2% pada teknik baku. Kata kunci: Kemudahan pemasangan, komplikasi, laryngeal mask airway, teknik baku disertai penekanan lidah, teknik baku LMA is one of the airway management device. Novel technique of LMA insertion combined with tongue supression technique resulted in 100% succes rate of insertion. The objective of this study was to compare easiness and complications of inserting LMA using classic approach combined with tongue supression and classic approach. This study was a single-blind randomized clinical trial conducted from May ̶June 2013 in RSCM on 80 adult patients who underwent elective surgery with general anesthesia using LMA. In 40 patients underwent LMA insertion with classic approached combined with tongue supression technique and 40 patients with classic approached. Effort and success rate was noted and evaluated. Insertion was considered easy if the insertion was attempted maximally twice. Complications such as blood stains, sore throat, and dysphagia was noted and evaluated. Statistical analysis conducted by Chi-square Test and Fischer Exact. P <0,05 was considered significant. Proportion of first and second attempt LMA insertion between both technique was 87,5% compared with 65% and 100% compared with 97,5%, respectively. LMA insertion with classic approached combined with tongue supression technique was not easier than with classic approached technique. Complication which statistically significant different was blood stains 0% with classic approached combined with tongue supression technique compared with 6,2% classic approached technique. Key words: Classic approached combined with tongue supression, classic approached technique easy installation complications, laryngeal mask airway Reference Sinha PK, Misra S. Supraglottic airway devices other than LMA and its prototypes. Indian J anaesth. 2005;49(4):281–92. Hein C, Owen H, Plummer J. Randomized comparison of the SLIPA and the SS-LM by medical students. Emergency Medicine Australasia. 2006;18:478–83. Basket PJF, Brain AIJ, Handbook of the use of LMA in CPR. Intavent. 1998:1–14. Hein C. The Prehospital practitioner and the LMA: are you keeping Up?. J Emerg Primary Health Care. 2004:2; 1–2. Brimacombe JR, Berry AM, Daves SM, The LMA, Airway Management. Dalam: Hanowel LH, Penyunting Lippincott: Raven Publishers, Philadelphia;1996. Hlm.195–221. Rieger A, Brunne B, Striebel W. Use of manometry for laryngeal mask airway reduces postoperative pharyngolaryngeal adverse events, a prospective randomize trial. Anesthesiol. 2010; 112:652–7. Park PG, Choi GJ, Kim WJ, Yang SY, Shin HY, Kang H, dkk, A comparative study among normal saline, water soluble gel and 2% lidocaine gel as a SLIPA lubricant, Korean J Anesthesiol. 2014 February; 66(2): 105–111. Hein C. The prehospital practitioner and the laryngeal mask airway: “Are you keeping up?”. Austral Jo Paramed. 2004:2 (1) Vaida S. Airway management-Supraglotic Airway Devices. Timisoara. 2004. Strydom C, Le Roux. A clinical comparison of disposable airway devices. SAJAA. 2008; 14(6):31–36. Andre AZ. Comparison of the LMA-Classic with the new disposable soft seal laryngeal mask in spontaneously breathing adult patients. Anesthesiology. 2003;99:1066–71. Keijzer C, Buitelaar D. A Comparison of postoperative throat and neck complaints after the use of I-gel and the La Premiere Disposable laryngeal mask: a double-blinded, randomized, controlled trial. Anaesth Analg 2009; 109(4);1092–4. Cook TM, Gatward et al. A Cohort evaluation of the I-Gel airway in 100 elective patients. J Association Anaesthetists Great Britain Ireland 2008;63:1124–30. Roodneshin F, Agah M, Novel technique for placement of LMA in difficult pediatric airways. Tanaffos.2011;10(2):56–8. Mun’im A. Perbandingan dua macam teknik pemasangan sungkup laring pada penderita operasi elektif di RSUPN-CM tahun 1997. [Tesis]. Jakarta: Departemen Anestesiologi dan Terapi Intensif FKUI/RSCM. 1997. Payne FB, Wilkes NC. A prospective study of two insertion techniques of the laryngeal mask airway. Anesthesiol. 1996;85:3A. Malayanti. Keberhasilan pemasangan sungkup laring: perbandingan antara teknik baku dengan teknik putar 180o pada pasien operasi elektif. [Tesis]. Jakarta: Departemen Anestesiologi dan Terapi Intensif FKUI/ RSCM. 2002. Brimacombe J, Berry AM, Insertion of the LMA A Prospective Study of Four Techniques. Anaesth Intens Care. 1993;21:89–92 (4).